1995
DOI: 10.1093/infdis/172.4.1126
|View full text |Cite
|
Sign up to set email alerts
|

Peru-15, an Improved Live Attenuated Oral Vaccine Candidate for Vibrio cholerae O1

Abstract: Cholera vaccine candidate Peru-15 was derived from a Vibrio cholerae O1 El Tor Inaba strain by deleting the cholera toxin genetic element, introducing the gene encoding cholera toxin B subunit into recA, and screening for nonmotility. In a controlled study, Peru-15 (2 x 10(8) cfu) was administered to 11 volunteers. No vaccinee developed diarrhea, and 10 of 11 had > 4-fold rises in vibriocidal antibody titers. One month later, 5 vaccinees and 5 control volunteers were challenged with wild type V. cholerae O1. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
112
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 11 publications
2
112
1
1
Order By: Relevance
“…Volunteers inoculated with Peru-3 often developed selflimiting diarrhea, whereas diarrhea was not observed in volunteers who received Peru-15 (6,7). Similarly, we found that most (12/18) rabbits inoculated with Peru-3 developed diarrhea, whereas only 2 of 13 rabbits inoculated with Peru-15 exhibited diarrhea.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Volunteers inoculated with Peru-3 often developed selflimiting diarrhea, whereas diarrhea was not observed in volunteers who received Peru-15 (6,7). Similarly, we found that most (12/18) rabbits inoculated with Peru-3 developed diarrhea, whereas only 2 of 13 rabbits inoculated with Peru-15 exhibited diarrhea.…”
Section: Resultssupporting
confidence: 73%
“…However, development of such vaccines has been hampered by their reactogenicity. The molecular bases of reactogenicity are not known, but it has been speculated, based on the absence of reactogenic diarrhea associated with Peru-15, a nonflagellated V. cholerae ctxA mutant, that symptoms are a response to V. cholerae's flagellum and/or the motility that it enables (7,8). Here, we used an infant rabbit model of reactogenicity to define better the V. cholerae factors that contribute to this host response to earlier vaccine prototypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Two major strategies have been used to develop a cholera vaccine with long-term immunity: live-attenuated V. cholerae strains lacking the ability to produce CT 5,7,8 and killed whole cell toxogenic V. cholerae strains in combination with CTB. [7][8][9] Several live-attenuated vaccine candidates have been developed including CVD103-HgR, CVD111, CVD101, CVD103, Peru-14, and Peru-15, which have been used in the clinical trials.…”
mentioning
confidence: 99%
“…[7][8][9] Several live-attenuated vaccine candidates have been developed including CVD103-HgR, CVD111, CVD101, CVD103, Peru-14, and Peru-15, which have been used in the clinical trials. 5,6,8,10,11 These are single dose vaccines, which can elicit a high titer of serum vibriocidal antibodies because they can actively colonize the host intestinal lumen. 6,[12][13][14] The major defect of the engineered live vaccine strains is the probability of acquiring the enterotoxin gene through horizontal gene transfer.…”
mentioning
confidence: 99%